Optimasi Waktu Perendaman dan Stadia Kematangan Buah Kakao untuk Meningkatkan Daya Kecambah dan Pertumbuhan Awal Bibit Kakao - Ahmad Rizky Pratama; Siti Nurhaliza Ramadhani (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to determine the effect of soaking duration and fruit maturity level on the germination and early growth performance of cocoa (Theobroma cacao L.) seeds. A completely randomized design (CRD) was employed with two factors: fruit maturity (physiologically mature, fully ripe, and overripe) and soaking duration (0, 6, 12, and 24 hours). Each treatment combination was replicated three times. The results showed that both fruit maturity and soaking duration significantly influenced seed germination percentage, seedling height, number of leaves, and root length. The highest germination rate (92.22%) and best growth parameters were obtained from seeds derived from fully ripe fruits soaked for 12 hours. Conversely, seeds from overripe fruits without soaking exhibited the lowest germination (51.11%). The optimal soaking treatment appears to enhance water uptake and enzymatic activity, which supports early seedling development, while excessive ripening reduces seed viability. These findings suggest that selecting the right maturity stage and appropriate soaking time can significantly improve the success rate of cocoa seed propagation.